Perfil de ácidos graxos, embutido fermentado e características da carcaça de ovelhas de descarte - Pelegrini, Luis Fernando Vilani de (2007)
The experiment was accomplished with the objective of determine the differences in the carcasses traits and the fatty acids profile in meats of culling sheep of two genetic groups in two feeding systems and also to evaluate fermented sausage type salami produced with this meat. Were used 20 culling ewes, being 10 of the Ideal race and 10 of the Texel race, which were randomly distributed in according to its genetic group, in two alimentary systems: feedlot and cultivated pasture of black oat (Avena strigosa Schreb.) + rye grass (Lolium multiflorum Lam.). The animals were slaughtered when they reached a medium corporal score of 3.5 points. The carcasses were kept in a freezer chamber for 24 hours before the evaluation. The fatty acids were analyzed by gas chromatoghaph after taken a Longissimus dorsi sample between the 12 and 13 ribs. For the production of the sausages a proportion of 80% of sheep meat was used (neck and forequarter) and 20% of pig ham. The pH determinations were accomplished, activity of water, reduction of weight and sensorial analysis, using a scale of 7 points, evaluating the color, odor, aroma and flavor attributes of the fermented sausages. The Texel animals showed hot carcass weight (HCW) and cold carcass weight (CCW), and hot carcass yield (RCY) and cold carcass yield (CCY) significantly highers (P<.05) than the Ideal animals, being the average values for the two races respectively 27.85 and 19.04 kg, 27.08 and 18.43 kg, 47.25 and 45.20% and 45.95 and 43.72%. In the same way, when expressed in absolute values (kg), the animals of the Texel race had presented significant superiority (P<.05) to the average values for leg, shoulder, neck and rib, as well as for the amounts of muscle, bone and fat of the leg. When expressed in relative values (%), however, significant differences between the two races had not been observed (P>.05) for these characteristics. The alimentary handling did not consist in an important cause of variation (P>.05) of the characteristics of the carcass of culling sheep. The major fatty acids present in Longissimus dorsi muscle of sheep in all treatments were the oleic (C18:1), palmitoleic (C16:0) and stearic (C18:0). The genetic group did not affect the fatty acids profile of this muscle. However, the content of ω3 fatty acids was higher (P<.05) and the ω6/ω3 ratio was lower (P<.05) in meat of sheep grazing the temperate pasture. Differences were not found among genetic groups (P>.05) and alimentary system (P>.05). The medium values in the sensorial panel, varied from 4.90 to 5.41 for the coloration; 4.53 to 4.81 for the odor; 5.25 to 5.75 for the flavor and from 5.40 to 5.69 for the texture and for the two feeding methods they varied from 5.03 to 5.25; 4.56 to 4.78; 5.50 and 5.34 to 5.75 for the coloration, odor, flavor and texture, respectively, considering the two genetic groups. Based on fatty acids profile, the sheep finished on temperate pasture provided a healthier meat for the human consumption than sheep managed as feedlot. It can be concluded that the sausages fermented with meat of sheep and suine a proportion of 80:20 were sensory approved for the tasters.